PENGEMBANGAN PERANGKAT WIRELESS SENSOR NETWORK UNTUK MENGONTROL TINGKAT VOLUME AIR PADA TURBIN - Hesti, Emilia (Universitas Muhammadiyah Palembang, 2021)
Wireless Sensor Network technology is a wireless network consisting of several individual sensor nodes that are used to monitor the condition of a place and can interact with its environment by means of sensing, controlling and communication of physical parameters. The application of Wireless Sensor Network Technology to the water turbine as a power plant is used for remote control and monitoring of the water turbine. So that it allows users to get maximum and real time information without having to be in the sensor area, in the sending and receiving of information using the Wireless HC-12 module with a frequency range of 432 MHz. HC12 Wireless Transceiver that can receive information on the Master Controller device and can send requests to the microcontroller on the server device. In this subsystem there is a MAX232 IC as a converter that converts the RS232 level signal from a TTL level signal on the HC12 Wireless module to a data communication that can be displayed on a computer. Keywords: Artificial Inteligent, Embedded System, Microkontroller, Visual Basic, Wireless Sensor Network